CASE-BASED REASONONG TECHNIQUES VS OTHER TECHNIQUES FOR RETRIEVING COMPONENTS - Dugalikj, Bisera; Velinov, Goran (My University, 2013)
Component retrieving methods have become essential in the process of finding the adequate component as a result to the constant increasing of the number of components that are presented on the market and the often difficulties in finding and recognizing the right component to match with the requirements of the user. In this paper we intend to identify and compare some of the better practices currently available in the process of retrieving components. Component-based software engineering is an area that has a constant progress and growth and it also has a huge expansion in production of components from many different vendors and not just from component libraries so the number of available components is considerably increasing. As a result, there are many component retrieval methods and each of them has their specific approach to the subject. This research is focused on several component retrieval methods including: traditional information retrieval like free-text-based documents, XML retrieval, pre-enumerated vocabulary method, signature matching method, behavior-based retrieval method, faceted selection and conversational component retrieval method (CCRM).